Prokaryotes Versus Eukaryotes: Who is Hosting Whom? - Tellez, Guillermo (Frontiers in Veterinary Science, 2014)
Microorganisms represent the largest component of biodiversity in our world. For millions of years, prokaryotic microorganisms have functioned as a major selective force shaping eukaryotic evolution. Microbes that live inside and on animals outnumber the animals’ actual somatic and germ cells by an estimated 10-fold. Collectively, the intestinal microbiome represents a ‘forgotten organ’, functioning as an organ inside another that can execute many physiological responsibilities. The nature of primitive eukaryotes was drastically changed due to the association with symbiotic prokaryotes facilitating mutual coevolution of host and microbe. Phytophagous insects have long been used to test theories of evolutionary diversification; moreover, the diversification of a number of phytophagous insect lineages has been linked to mutualisms with microbes. From termites and honey bees to ruminants and mammals, depending on novel biochemistries provided by the prokaryotic microbiome, the association helps to metabolize several nutrients that the host cannot digest and converting these into useful end products (such as short chain fatty acids), a process which has huge impact on the biology and homeostasis of metazoans. More importantly, in a direct and/or indirect way, the intestinal microbiota influences the assembly of gut-associated lymphoid tissue, helps to educate immune system, affects the integrity of the intestinal mucosal barrier, modulates proliferation and differentiation of its epithelial lineages, regulates angiogenesis, and modifies the activity of enteric as well as the central nervous system,. Despite these important effects, the mechanisms by which the gut microbial community influences the host’s biology remains almost entirely unknown. Our aim here is to encourage empirical inquiry into the relationship between mutualism and evolutionary diversification between prokaryotes and eukaryotes which encourage us to postulate: Who is hosting whom?